2013
DOI: 10.1371/journal.pone.0080859
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ginsenoside Rb1 against Intestinal Ischemia-Reperfusion Induced Acute Renal Injury in Mice

Abstract: Ginsenoside Rb1 (RB1), the most clinically effective constituent of ginseng, possesses a variety of biological activities. The objectives of this study were to investigate the protective effects of RB1 and its underlying mechanism on renal injury induced by intestinal ischemia-reperfusion (IIR) in mice. RB1 was administered prior to inducing IIR achieved by occluding the superior mesenteric artery for 45 min followed by 120 min of reperfusion. All-trans-retinoic acid (ATRA) was used as an inhibitor of NF-E2-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Upon activation, Nrf2 is relieved from Keap1-directed degradation, followed by nuclear translocation and subsequent binding to the antioxidant responsive element (ARE), eventually leading to the activation of a series of antioxidant and phase II enzymes. 107,108 To date, several ginsenosides, including Rb1, [109][110][111][112][113][114][115][116] Rg3, 95,[117][118][119][120] Rg1, 115,121,122 Rd, 123 Rh1, 124 and 20(S)protopanaxatriol, 115 were found to activate the Nrf2 pathway, whereas Rg3 was also shown to inhibit the Nrf2 pathway 125 (Fig. 4).…”
Section: Nrf2 Pathway and The Effect Of Ginsenosidesmentioning
confidence: 98%
See 1 more Smart Citation
“…Upon activation, Nrf2 is relieved from Keap1-directed degradation, followed by nuclear translocation and subsequent binding to the antioxidant responsive element (ARE), eventually leading to the activation of a series of antioxidant and phase II enzymes. 107,108 To date, several ginsenosides, including Rb1, [109][110][111][112][113][114][115][116] Rg3, 95,[117][118][119][120] Rg1, 115,121,122 Rd, 123 Rh1, 124 and 20(S)protopanaxatriol, 115 were found to activate the Nrf2 pathway, whereas Rg3 was also shown to inhibit the Nrf2 pathway 125 (Fig. 4).…”
Section: Nrf2 Pathway and The Effect Of Ginsenosidesmentioning
confidence: 98%
“…To date, several ginsenosides, including Rb1, Rg3, Rg1, Rd, Rh1, and 20( S )‐protopanaxatriol, were found to activate the Nrf2 pathway, whereas Rg3 was also shown to inhibit the Nrf2 pathway (Fig. ).…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
“…Ginsenosides are major components of the traditional herbal medicine ginseng, and ginsenosides can be classified into panaxadiols (PPD) and panaxatriols (PPT) by chemical structure. Rb1, the most abundant constituent of panaxadiol, has recently been reported to exert protective properties in vascular diseases and kidney diseases . A clinical study indicated that Rb1 alleviated creatine and inflammatory cytokine levels in CKD patients .…”
Section: Introductionmentioning
confidence: 99%
“…Rb1, the most abundant constituent of panaxadiol, has recently been reported to exert protective properties in vascular diseases and kidney diseases. [14][15][16][17] A clinical study indicated that Rb1 alleviated creatine and inflammatory cytokine levels in CKD patients. 18 Furthermore, it has been reported that Rb1 reduced type I collagen expression through PPAR-δ, which is considered an osteogenic profile marker of VSMC.…”
mentioning
confidence: 99%
“…Nrf2-mediated HO-1 induction contributes to antioxidant capacity has been demonstrated by multiple disease models, including cardiomyopathy in type 2 diabetic mice (Zhang et al 2014b), rat model of transient global cerebral ischaemia (Lee et al 2014), and endotoxic shock-induced acute lung injury in rabbits (Yu et al 2014). Recently, Nrf2/HO-1 activation also shows protective effect in aristolochic acid-induced acute kidney injury (Wu et al 2014a) and intestinal ischemia-reperfusion induced acute renal injury (Sun et al 2013). …”
Section: Introductionmentioning
confidence: 99%